Enhanced permeation, leaf retention, and plant protease inhibitor activity with bicontinuous microemulsions - Tamhane, Vaijayanti A.; Dhaware, Deepika G.; Khandelwal, Neha; Giri, Ashok P.; Panchagnula, Venkateswarlu (Journal of Colloid and Interface Science, 2012)
Bicontinuous microemulsions (BCMEs) have excellent solubulizing properties along with low interfacial tension and aqueous content that can be controlled. In this work, water soluble plant protease inhibitor (PI), well characterized for its activity against insect pests, was incorporated into a BCME system and explored for permeation on hydrophobic leaf surfaces and protease inhibition activity. The bicontinuous nature of the microemulsion containing water:2-propanol:1-butanol (55:35:10 w/w) was characterized using conductivity and self-diffusion coefficient measurements. The PI was soluble in the water-rich bicontinuous domains, stable in the microemulsions, and protease inhibition activity was retained for a prolonged duration. The microemulsions ensured greater wettability and a wider spread of the PI on hydrophobic leaf surfaces as revealed by contact angle measurements. Significantly, trypsin inhibition activity assays of the PI recovered from the leaves after delivery from the microemulsion indicated a significant increase in the PI retention on the leaf. This BCME enabled greater leaf permeation and retention of the PI can be attributed to a temporary disruption of the waxy leaf surface followed by self-repair without causing any long term damage to the plant. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Bicontinuous microemulsion; Biopesticide; Microemulsion pesticide; protease inhibitor; Protein encapsulation; Protein permeation

Matrix-assisted laser desorption/ionization mass spectrometry analysis of dimethyl arginine isomers from urine - Bhattacharya, Nivedita; Singh, Ajeet; Ghanate, Avinash; Phadke, Gayatri; Parmar, Dharmesh; Dhaware, Deepika G.; Basak, Trayambak; Sengupta, Shantanu; Panchagnula, Venkateswarlu (Analytical Methods, 2014)
Isomeric asymmetric and symmetric dimethyl arginine (ADMA and SDMA respectively) residues are excreted in urine and are putative markers of cardiovascular and chronic kidney diseases. In this work, we demonstrate simultaneous and quantitative detection of endogeneous ADMA and SDMA from urine samples of healthy subjects using MALDI-TOF MS without any chromatographic separation. The DMA isomers yielded [M + H](+) ions along with their product ions formed due to MALDI in-source fragmentation. The precursor ions were validated using MALDI-TOF MS/MS as well as direct injection ESI-Q-TOF MS/MS. ADMA and SDMA generated unique product ions at similar to m/z 46 and similar to m/z 172 respectively in the MS-mode itself. These were advantageously used for full scan-mode absolute quantification of the isomeric metabolites. The m/z observed for all the ions was within 10 ppm mass accuracy. The calibration method was established by generating internal standard normalized peak area-based concentration response curves using synthetic standards. Good linearities (R-2 > 0.95) with acceptable intra-assay, inter-assay variation (within 15% RSD) and excellent recoveries were observed for quality control samples. Finally, endogeneous concentrations of the metabolites were determined in urine from healthy subjects (n = 11). ADMA and SDMA were found to be in the range of 1.6-8 mu M and 2.9-9.1 mu M in urine and were in agreement with previously reported physiological levels.